Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.4039/n03-067
|View full text |Cite
|
Sign up to set email alerts
|

Undersowing rutabaga with white clover: impact on Delia radicum (Diptera: Anthomyiidae) and its natural enemies

Abstract: The cabbage maggot, Delia radicum (L.), is a serious pest of cruciferous crops in temperate regions of North America and Europe. The effects of undersowing rutabaga, Brassica napus L. subsp. rapifera Metzg. (Brassicaceae), with white clover, Trifolium repens L. (Leguminosae), on second-generation cabbage maggot and its natural enemies were studied in Newfoundland in 1997 and 1998. In 1997, totals of 1311 and 724 eggs were recovered from bare and undersown plots, respectively. More eggs were present in bare plo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…adults initially locating canola monocultures or intercrops with wheat were similar, as Bjö rkman et al (2007) also concluded for D. floralis. In agreement with our results, Dixon et al (2004) usually found nonsigniÞcant differences in D. radicum trapped in rutabaga (Brassica napus L. subsp. rapifera Metzg.)…”
Section: Analysis Of Variance For Canola Taproot Damage Data From Fsupporting
confidence: 94%
See 2 more Smart Citations
“…adults initially locating canola monocultures or intercrops with wheat were similar, as Bjö rkman et al (2007) also concluded for D. floralis. In agreement with our results, Dixon et al (2004) usually found nonsigniÞcant differences in D. radicum trapped in rutabaga (Brassica napus L. subsp. rapifera Metzg.)…”
Section: Analysis Of Variance For Canola Taproot Damage Data From Fsupporting
confidence: 94%
“…In studies intercropping brassicaceous vegetables with nonhost plants, where monocultures and intercrops had equal densities of host plants, researchers also found reduced Delia spp. egg densities in the intercrops (Tukahirwa and Coaker 1982, Finch et al 2003, Dixon et al 2004, Bjö rkman et al 2007. Similarly, reduced root maggot egg populations per plant were observed by Dosdall et al (2003) in weedy compared with weed-free canola with equivalent canola plant densities in the weedy and weed-free situations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The focal species in this study, the turnip root fly ( D. floralis ) and its congener the cabbage root fly ( Delia radicum L.), are herbivores on cruciferous crops. The cabbage root fly has been frequently studied for its potential to be controlled by intercropping (Theunissen et al., 1995; Finch & Kienegger, 1997; Lehmus et al., 1999; Dixon et al., 2004). The two species have similar biology and behaviour and react upon the same or related stimuli (Varis, 1967; Baur et al., 1996a).…”
Section: Methodsmentioning
confidence: 99%
“…; Dixon et al . ), there have been no reports of D. radicum in natural invasive‐range populations of B. nigra . Invasive B. nigra has thus likely escaped D. radicum .…”
Section: Methodsmentioning
confidence: 99%